Russian Colonization of Alaska : From Heyday to Sale, 1818-1867 - Grinëv, A. V. (Andreĭ Valʹterovich) (Book collections on Project MUSE., 2022)
"In "Russian Colonization of Alaska: From Heyday to Sale, 1818-1867," Andrei Val'terovich Grinëv examines the final period in the history of Russian America from the coming to power in the colonies of naval officers (1818) to the sale of Alaska to the United States (1867)"--